2013 IEEE Intelligent Vehicles Symposium (IV) 2013
DOI: 10.1109/ivs.2013.6629603
|View full text |Cite
|
Sign up to set email alerts
|

Driver classification and driving style recognition using inertial sensors

Abstract: Abstract-Currently there are many research focused on using smartphone as a data collection device. Many have shown its sensors ability to replace a lab test bed. These inertial sensors can be used to segment and classify driving events fairly accurately. In this research we explore the possibility of using the vehicle's inertial sensors from the CAN bus to build a profile of the driver to ultimately provide proper feedback to reduce the number of dangerous car maneuver. Braking and turning events are better a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(114 citation statements)
references
References 16 publications
0
109
0
5
Order By: Relevance
“…Lastly, Van Ly et al attempted to perform driver identification distinguishing between two drivers using sensor data collected from inertial sensors in a mobile device [28]. This work initially shows that a mounted phone sensor's accelerometer is highly correlated with acceleration and braking activity, and subsequently the authors use the phone data to distinguish between the two drivers along a diverse multi-hour course involving residential and highway segments (using a modern sedan).…”
Section: Related Workmentioning
confidence: 99%
“…Lastly, Van Ly et al attempted to perform driver identification distinguishing between two drivers using sensor data collected from inertial sensors in a mobile device [28]. This work initially shows that a mounted phone sensor's accelerometer is highly correlated with acceleration and braking activity, and subsequently the authors use the phone data to distinguish between the two drivers along a diverse multi-hour course involving residential and highway segments (using a modern sedan).…”
Section: Related Workmentioning
confidence: 99%
“…A number of previous studies have shown that drivers can be uniquely identified using driving behavior signals [7,8,11,16,17]. A variety of sensors can be found in off-the-shelf devices Journal of Advanced Transportation 3 available in current market.…”
Section: Driver Identification In Real-world Situationsmentioning
confidence: 99%
“…More recently proposed algorithms use Support Vector Machine (SVM) and are more focused in using driving behavior signals as inputs [10,16]. In [16], signals from inertial sensors, namely, accelerometer and gyroscope, are processed in order to detect accelerating, braking, and wheel-turning events.…”
Section: Driver Identification In Real-world Situationsmentioning
confidence: 99%
“…Firstly, obtaining a gravity vector with the vehicle stopped and, secondly, obtaining a driving directional vector and correcting it by a Principal Component Analysis (PCA) approach. Other authors try to use a fixed Inertial Measurement Unit on the vehicle [12] or they use a smartphone in a fixed and calculated position in [13,14].…”
Section: Introductionmentioning
confidence: 99%